Analysis of genetic diversity in sesame (Sesamum indicum L.) germplasm lines based on agro-morphological traits and SSR markers - Md. Ashfaq1*, K. Jhansi Rani2, D. Padmaja3, Praduman Yadav4 and Usha Kiran Betha5 (Electronic Journal of Plant Breeding)
An investigation was carried out with a set of fifty sesame genotypes to study the degree of genetic diversity based on morphological and marker based genotypic data. The genomic isolation was carried out using CTAB method and the molecular diversity was estimated with the help of fifty SSR markers using per cent polymorphism, PIC content and represented in dendogram. Morphological diversity was estimated by using D2 analysis. Quantitative traits, namely plant height (67.8-147.2 cm), number of capsules per plant (36-89), number of seeds per capsule (46-70), seed yield per plant (3.20-10.89 g), oil content (40.64-50.51 %), protein content (20.5-32.42 %), oleic acid content (31.25-42.85 %) and linoleic acid content (40.39-54.11 %) showed a significant amount of variation. Fifty genotypes were grouped into fourteen clusters based on data of 15 agro-morphological traits by following Tocher′s method. SSR markers showed 36% polymorphism with an average of 2.39 alleles per locus and 0.34 PIC value indicated a trend of moderate level of genetic diversity at molecular level in the collection of genotypes. In order to assess genetic diversity and to select various lines for breeding programs, the results highlighted the importance of utilizing both agro-morphological and molecular data.